Dominio de técnicas secretariales y su efecto en la redacción comercial en las secretarías de la Corporación de Manejo Seguro de la ciudad de Guayaquil - Mera Cañarte, Raiza Annabel (2022)
The research topic addressed in this case study refers to the mastery of secretarial techniques and their effects on the commercial writing of the staff of the Safe Management Corporation located in the City of Guayaquil. It is essential to highlight the need to propose research on these topics since the application of secretarial techniques has great relevance in the administrative field, therefore, the improvement of the same will greatly benefit the exercise of the functions of professionals who carry out activities in the secretarial area, as it is in this case, business writing. The objective of this project will be fulfilled by developing the variables and their derived subtopics, through documentary-bibliographical research, relying on theoretical support from credible official scientific sources. For its part, the collection of first-hand information will be obtained through the use of the survey technique. Through an instrument such as the questionnaire, strategically designed questions are raised to gather the findings that allow in-depth problems for further analysis and interpretation. This is how this research is concluded, carefully developing each stage of it, from the theoretical precepts supported by authors to the findings collected through the survey. It is obtained thanks to the fact that the employees of the Safe Driving Corporation have little or no knowledge about secretarial techniques, this consequently affects the business writing process in the company, and is due to various factors that are detailed in greater detail in the development of this study.